TOKOH DALAM NAMA-NAMA JALUR DI KUANTANSINGINGI - Raja Saleh (Madah: Jurnal Bahasa dan Sastra, 2013)
The problem in this research is how the naming system of long boat in Kuantansingingi is. The research, entitled "The Figures in Long Boat Names in Kuantansingingi" aims to describe the naming system in the long boat in Kuantansingingi. The data were collected by inventorying names of each long boat participating in the “Pacu Jalur” festival, Telukkuantan, 2012. The author focuses only on the long boat with the figures name. The data were analyzed by using the descriptive analytical method based on the theory of Dessausure. The research findings show that the names of the figures are used because the owners of long boats hope that their long boats also have superiority such as the figures. The figure’s names used are pendekar, dubalang, raja, pangeran, putra/putri, sutan, panglimo, juragan, and panji. The naming system of long boast in Kuantansingingi is done  through a village meeting by considering several things, including the geographical situation of the village such as lakes, rivers, and forests as well as legends or fairy tales, such as the legends about animals, figures, and so on that exist in their villages.  Masalah dalam penelitian ini adalah bagaimana sistem penamaan jalur di Kuantansingingi. Penelitian yang berjudul “Tokoh dalam Nama-nama Jalur di Kuantansingingi” ini bertujuan untuk mendeskripsikan sistem penamaan jalur di Kuantansingingi. Data dikumpulkan dengan menginventarisasi setiap nama jalur yang ikut dalam festival pacu jalur di Telukkuantan tahun 2012. Penulis hanya memfokuskan kepada nama jalur yang memiliki nama tokoh. Penganalisisan data dilakukan dengan menggunakan metode deskriptif analitis yang mengacu pada teori Dessausure. Penelitian ini menunjukkan bahwa nama-nama tokoh digunakan karena para pemilik jalur berharap agar jalur mereka juga memiliki keunggulan-keunggulan seperti tokoh tersebut. Nama-nama tokoh yang digunakan adalah pendekar, dubalang, raja, pangeran, putra/putri, sutan, panglimo, juragan, panji. Sistem penamaan jalur di Kuantansingingi adalah melalui rapat desa dengan mempertimbangkan beberapa hal, di antaranya keadaan geografis desa seperti danau, sungai, dan hutan yang ada di desa mereka serta legenda atau dongeng yang berkembang di desa tersebut, seperti legenda tentang binatang, tokoh, dan sebagainya.